How to Make Decisions of Gen Z Travelers? Exploring The Influence of Perceived Risk, Online Review, and Price on Travel in Bali - Aryasih, Putu Ayu; Puja, Ida Bagus Putu; Gunawan, Made Krishna Wira; Priharjuna, Brahmantya Agung; Putra, I Made Mahendra (Devotion : Journal of Research and Community Service, 2023)
This study aims to examine how to make decisions of Gen Z influence of the current COVID-19 public health crisis on consumer risk perceptions, and what is more significant is how risk perceptions have the potential to influence tourist post-crisis recovery travel behavior. The research sample had 250 respondents. Baby Boomers, Gen Xers, and Millennials value input from their Gen Z kids. Gen Z is an individual from the most recent generation born between 1995 and early 2012. Multiple linear regression analysis was employed in this quantitative study. The result was: (1) Perceived Risk has no effect on Gen Z Travel Decision which a coefficient value is 0.061 (2) e-WOM Argument Quality (Online Review) has significantly influenced Gen Z Travel Decision which a coefficient value of 0.394 (3) Price has no effect on Gen Z Travel decision which the coefficient value is 0.375. The goal of the growth strategy is to increase sales, assets, earnings, or a combination of the three. This can be done through reducing costs, creating new items, improving the quality of existing products or services, or gaining access to a larger market. That approach may be used in other places that could become popular tourist destinations.